Bisexual Identity in a Religious Environment in Christina Lauren’s Autoboyography - A. Sasli, Siti Atiqahgania; Setiawan, Ikwan; Salikin, Hairus (MOZAIK HUMANIORA, 2024)
This study focuses on analyzing the representation of bisexual identity in Christina Lauren’s novel "Autoboyography." Through qualitative research, the aim is to reveal the discourse of bisexuality constructed by the acts and behaviors of other characters toward the male main characters using Stuart Hall’s theory of representation, with a particular focus on Michel Foucault’s discursive approach. Another objective of this study is to examine the critical position of Christina Lauren as the novel’s author towards the issue of bisexuality. The findings reveal that the author created characters who both oppose and support bisexuality, thereby highlighting the issue of bisexuality in the 21st century. Through their narrative, the author sheds light on the challenges faced by male individuals living as bisexuals in a religiously conservative environment. By doing so, Christina Lauren not only addresses social issues surrounding bisexuality but also illustrates the main character's struggles in accepting a bisexual identity in an environment influenced by religious beliefs.